Synthesis characterisation and neuroprotectivity of Silybum marianum extract loaded chitosan nanoparticles - Ay, Hatice Feyzan; Yesilkir-Baydar, Serap; Cakir-Koc, Rabia (TAYLOR & FRANCIS LTD, 2023)
AimSilybum marianum extract (SME) possesses neuroprotective potency through its high antioxidant content. We attempted to increase the effectiveness of SME by encapsulating them in chitosan. Neuroprotective potency of SME and SME-loaded chitosan nanoparticles (SME-CNPs) were shown in SH-SY5Y cell line against H2O2-induced oxidative stress.MethodsWe produced CNPs and SME-CNPs by ionic gelation method and properly determined their physical characteristics. Encapsulation efficiency, loading capacity, and in vitro release tests were performed for SME-CNPs. The neurotoxicity and neuroprotective efficiency in SH-SY5Y cell line against H2O2 was also investigated.ResultsThe size of SME-CNPs was 168.2 +/- 11.12 nm with zeta potential 10.6 +/- 1.0 mV. The encapsulation efficiency and loading capacity were successfully achieved at 96.6% and 1.89% respectively. SME and SME-CNPs improved cell viability higher than 80%, and SME-CNPs exhibited significant neuroprotective effects against H2O2 damage.ConclusionsIt was concluded that SME and SME-CNPs highly prevent damage caused by H2O2 and reduce cell damage in vitro by their neuroprotective effects.
Keywords: Alzheimer's disease; chitosan nanoparticles; encapsulation; ionic gelation; neuroprotective effect; oxidative damage; Silybum marianum extract; STRATEGIES; GELATION; ASSAYS; CELLS; Chemistry; Engineering; Pharmacology & Pharmacy